Acute kidney injury predicts all‐cause mortality in patients with cancer. (9th April 2019) - Kang, Eunjeong; Park, Minsu; Park, Peong Gang; Park, Namyong; Jung, Younglee; Kang, U; Kang, Hee Gyung; Kim, Dong Ki; Oh, Kook‐Hwan; Joo, Kwon Wook; Kim, Yon Su; Yoon, Hyung-Jin; et al.
Abstract: Background: Acute kidney injury (AKI) is a critical issue in cancer patients because it is not only a morbid complication but also able to interrupt timely diagnostic evaluation or planned optimal treatment. However, the impact of AKI on overall mortality in cancer patients remains unclear. Methods: We conducted a retrospective cohort study of 67 986 cancer patients, from 2004 to 2013 to evaluate the relationship between AKI and all‐cause mortality. We used KDIGO AKI definition and grading system. Results: During 3.9 ± 3.1 years of follow‐up, 33.8% of the patients experienced AKI at least once. Among AKI events, stage 1, 2, and 3 was 71.0%, 13.8%, and 15.1%, respectively. AKI incidence was highest in hematologic malignancies, followed by urinary tract cancer, and hepatocellular carcinoma. Male sex, older age, underlying diabetes and hypertension, lower serum albumin and plasma hemoglobin, more frequent radio‐contrast exposure, entrance of clinical trials, and receiving chemotherapy were associated with AKI occurrence. AKI development was an independent risk factor for elevated mortality in cancer patients with dose‐responsive manner (Stage 1, hazard ratio [HR] 1.183, 95% confidence interval [CI] 1.145‐1.221, P  < 0.001; Stage 2, HR 1.710, 95% CI 1.629‐1.796; Stage 3, HR 2.000, 95% CI 1.910‐2.095; No AKI, reference group) even after adjustment. This tendency was reproduced in various cancer types except thyroid cancer and in various treatment modalities, however, not shown in patients with baseline renal dysfunction. Conclusion: AKI was an independent risk factor for all‐cause mortality in overall cancer patients with dose‐responsive manner. Abstract : Acute kidney injury (AKI) is a critical issue in cancer patients because it is not only a morbid complication but also able to interrupt timely diagnostic evaluation or planned optimal treatment. In this study, AKI was an independent risk factor for all‐cause mortality in overall cancer patients with dose‐responsive manner.